Effective Ways to Resolve Marital Conflicts from a Christian Faith Perspective - Caraty, Lily; Paulus, Yanto; Suprandono, Yohanes; Deak, Victor; Nidin, Solihin Bin (PT FORMOSA CENDEKIA GLOBAL, 2025)
Marriage today is highly vulnerable to divorce due to unresolved conflicts. Husbands and wives need to understand the causes of conflict and how to resolve them in order to have a harmonious married life based on the Christian faith perspective. The method used in writing this journal is a literature study, drawing from statistical data, surrounding phenomena, and ways to resolve conflict according to the Bible. Through understanding the causes and solutions to conflict, it is hoped that this can benefit married couples by helping them build a strong marriage and grow in their knowledge and application of God's Word in their marital life.